x : x +13 = 14
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
x=13 nên x+1=14
\(f\left(x\right)=x^{14}-x^{13}\left(x+1\right)+x^{12}\left(x+1\right)-...+x^2\left(x+1\right)-x\left(x+1\right)+14\)
\(=x^{14}-x^{14}-x^{13}+x^{13}-...+x^3+x^2-x^2-x+14\)
=14-x=1
x=13 nên x+1=14
f(x)=x14−x13(x+1)+x12(x+1)−...+x2(x+1)−x(x+1)+14f(x)=x14−x13(x+1)+x12(x+1)−...+x2(x+1)−x(x+1)+14
=x14−x14−x13+x13−...+x3+x2−x2−x+14=x14−x14−x13+x13−...+x3+x2−x2−x+14
=14-x=1
a: \(=\dfrac{17}{19}\cdot\dfrac{19}{17}\cdot\dfrac{4}{5}=\dfrac{4}{5}\)
b: \(=\dfrac{14}{7}\cdot\dfrac{7}{6}=2\cdot\dfrac{7}{6}=\dfrac{14}{6}=\dfrac{7}{3}\)
c: =13/14(4/5+1/5)=13/14
\(\dfrac{17}{19}\times\dfrac{12}{15}\times\dfrac{19}{17}.\\ =\dfrac{17}{19}\times\dfrac{19}{17}\times\dfrac{12}{15}.\\ =1\times\dfrac{12}{15}=\dfrac{12}{15}.\\ \left(\dfrac{5}{7}+\dfrac{9}{7}\right)\times\dfrac{21}{18}.\\ =2\times\dfrac{7}{6}=\dfrac{7}{3}.\\ \dfrac{4}{5}\times\dfrac{13}{14}+\dfrac{13}{14}\times\dfrac{1}{5}.\\ =\left(\dfrac{4}{5}+\dfrac{1}{5}\right)\times\dfrac{13}{14}.\\ =1\times\dfrac{13}{14}.\\ =\dfrac{13}{14}.\)
X=VÔ SỐ